Simple and effective method of heat therapy in lymphoedema - Kulkarni, Ananta A. (Springer-Verlag, 2010)
Heat therapy is a well known conservative management for lymphoedema. We are describing here a heat therapy apparatus which is easy to make, cheap, transportable, easily reproducible and maintenance free and found to be very effective.